The effects of magnesium supplementation in autoimmune rheumatic diseases - Aaron Lerner; Jozélio Freire de Carvalho; Carina Benzvi; Motti Haimi (Academia Medicine)
Magnesium is an essential mineral for the human body, and its deficiency causes multiple detrimental cellular and organ dysfunctions. The issue of its routine supplementation is debatable, but there is no doubt that in case of depletion, it should be supplemented. Because of its role in inflammatory and autoimmune conditions, its serum levels have been frequently analyzed. However, its role in rheumatological diseases has been barely investigated. The present review aims to screen the literature for well-designed studies in which magnesium was supplemented to cure rheumatological conditions. SciELO, PubMed, and Web of Science databases were screened between 1966 and April 2024 for the literature on this topic. Only one study fulfilled the inclusion criteria and demonstrated that 300 mg/day of oral magnesium reduced insulin resistance in rheumatoid arthritis patients. The lack of studies on this subject shows that additional studies are required to understand the causal relationship between magnesium supplementation and disease treatment.